Women in the Historical Reflection of Paweł Jasienica on the Example of the Book on the Title: Ostatnia z rodu (The Last of the Family) - Kolbuszewska, Jolanta (Sensus Historiae, 2019)
Ostatnia z rodu (The Last of the Family) was a unique work in the achievements of Jasienica, not only because of making the main character of woman, but also focusing on an individual hero. The historian undertook in it a polemic with current way of presenting and evaluating Anna Jagiellonka functioning in the Polish literature. To show the specifics and originality of his approach, the Author began with comments on the image of Anna which dominated in Polish historiography of the nineteenth and twentieth centuries. There were analyzed the syntheses of Polish history and monographs devoted to the Jagiellonian dynasty. Presenting Jasiennica’s views, Jolanta Kolbuszewska also referred to the monograph of Maria Bogucka (Annna Jagiellonka), published in 1964.